2016
DOI: 10.1080/10408398.2016.1230088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antimicrobial use in agricultural animals on drug-resistant foodborne salmonellosis in humans: A systematic literature review

Abstract: Controversy continues concerning antimicrobial use in food animals and its relationship to drug-resistant infections in humans. We systematically reviewed published literature for evidence of a relationship between antimicrobial use in agricultural animals and drug-resistant meat or dairy-borne non-typhoidal salmonellosis in humans. Based on publications from the United States (U.S.), Canada, and Denmark from January 2010 to July 2014, 858 articles received title and abstract review, 104 met study criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 90 publications
1
26
0
1
Order By: Relevance
“…75 Suspected principal foci of selection pressure include use of antimicrobials for the treatment of humans and in food-producing animals for treatment or prevention of disease and growth promotion. 75,76 Modern molecular methods combined with other conventional techniques such as pulse field gel electrophoresis can be used to investigate the origins of foodborne human enteric disease and the role of antimicrobial use in cattle with the occurrence of multiple drug-resistant Salmonella infection in humans. At this point in time, there are few published studies establishing such links from "farm to fork."…”
Section: Public Health Concerns With Salmonella and The Dairy Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…75 Suspected principal foci of selection pressure include use of antimicrobials for the treatment of humans and in food-producing animals for treatment or prevention of disease and growth promotion. 75,76 Modern molecular methods combined with other conventional techniques such as pulse field gel electrophoresis can be used to investigate the origins of foodborne human enteric disease and the role of antimicrobial use in cattle with the occurrence of multiple drug-resistant Salmonella infection in humans. At this point in time, there are few published studies establishing such links from "farm to fork."…”
Section: Public Health Concerns With Salmonella and The Dairy Industrymentioning
confidence: 99%
“…73 A recent extensive systematic literature review of 858 publications on the effect of antimicrobial use in agricultural animals on drug-resistant foodborne salmonellosis in humans from 2010 to 2014 concluded that, although antibiotic use in cattle increased the likelihood of colonization in the host, there were no studies that traced antimicrobial-resistant Salmonella in humans back to the farm. 76 The antimicrobials of choice for treating bacterial gastroenteritis in humans are generally the fluoroquinolone, ciprofloxacin, for adults and the cephalosporin, ceftriaxone, for children. 63,77 At issue today is whether the veterinary analogs of these drugs may be responsible for the emergence of antimicrobial resistance in foodborne pathogens like Salmonella.…”
Section: Public Health Concerns With Salmonella and The Dairy Industrymentioning
confidence: 99%
“…There is general agreement that widespread antimicrobial use creates conditions that can select for the expression and exchange of resistance genes in pathogenic and commensal bacteria. Yet, the relative contributions of antimicrobial use in veterinary and human medicine to the emergence of resistant infections in people are not fully understood (Government of Canada, ; Helke et al, ; Hoelzer et al, ; WHO, ). Globally, fluoroquinolone use in broiler chickens was linked with fluoroquinolone‐resistant Campylobacter infections in people (Cheng et al, ; Endtz et al, ; Gupta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Negative impacts on the soil microbial ecology or microbiome has direct implications for food systems (Wall et al, 2015;Andriuzzi et al, 2018). CEC impacts the natural regulation of infectious diseases by exposing humans to animal-borne pathogens, and promoting antimicrobial resistance indirectly as a result of antibiotic use in animal agriculture (McCrakin et al, 2016;Helke et al, 2017). CEC also impacts food safety: rises in temperature and changing precipitation patterns can impact the presence of bacteria, viruses, and parasites responsible for food-borne diseases and zoonotic diseases; flooding and droughts can contaminate agricultural soils (Tirado et al, 2010).…”
Section: Impact Of Cec On Biodiversitymentioning
confidence: 99%